Development, Structure, Mechanism and Efficacy of Trypanocidal for Surra - Subekti, Didik T (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Surra is a contagious disease due to Trypanosoma evansi infection and causes economic loss in animal husbandry, especially in African countries, South America, the Middle East and Asia. In Indonesia, in 2010 to 2011 Trypanosoma outbreak resulted in death of 1159 horses, 600 buffaloes and a cattle. Control of Surra is generally done by using trypanosidal for eradication of parasites in animals. Trypanosidal for Surra is still relying five drugs namely suramin, isometamidium, quinapyramine, diminazene and melarsomine. The drugs have been used since 1920 until now. Suramin, quinapyramine and isometamidium can be used for curative or prophylactic purposes due to the long elimination half-life in the body, while diminazene and melarsomine are applied just for curative purposes. The efficacy of trypanosidal is largely determined by the sensitivity of T. evansi strain which is existed in their area and should not be generalized. Key words: Trypanocidal, Surra, Trypanosoma evansi